2024
DOI: 10.3389/fcvm.2024.1276521
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of spontaneous coronary artery dissection: a systematic review of the literature

Milovan Petrović,
Tatjana Miljković,
Aleksandra Ilić
et al.

Abstract: BackgroundContemporary management of spontaneous coronary artery dissection (SCAD) is still controversial. This systematic review of the literature aims to explore outcomes in the patients treated with conservative management vs. invasive strategy.MethodsThe PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed when we extensively searched three electronic databases: PubMed, ScienceDirect, and Web of Science, for studies that compared conservative vs. invasive rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A retrospective study of 53 SCAD patients showed a lower revascularization success rate but overall better survival in conservative versus PCI strategy than patients with atherosclerotic ST-segment elevation MI (STEMI) [50]. PCI intervention conveys a high rate of periprocedural failure and complications such as secondary iatrogenic dissections or intramural hematoma advancement by the PCI wires in existing feeble coronary structures [48,49,[51][52][53]. Larger sample retrospective studies and meta-analyses conducted have further noted a failure rate of 35-53% with PCI strategy and urgent referral to coronary artery bypass grafting (CABG) in 9-13% of patients.…”
Section: Revascularization Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of 53 SCAD patients showed a lower revascularization success rate but overall better survival in conservative versus PCI strategy than patients with atherosclerotic ST-segment elevation MI (STEMI) [50]. PCI intervention conveys a high rate of periprocedural failure and complications such as secondary iatrogenic dissections or intramural hematoma advancement by the PCI wires in existing feeble coronary structures [48,49,[51][52][53]. Larger sample retrospective studies and meta-analyses conducted have further noted a failure rate of 35-53% with PCI strategy and urgent referral to coronary artery bypass grafting (CABG) in 9-13% of patients.…”
Section: Revascularization Modalitiesmentioning
confidence: 99%
“…The prevalence of MACE measured over 25 years was around 24% with a decreased need for intensive care admissions [73]. However, in a recent larger systematic review, MACE was reportedly increased with SCAD recurrence in 31%, ACS in 27.4%, target vessel revascularization in 30%, and others such as repeat stenting, unstable angina, heart failure, and stroke [53]. An additional benefit observed in the dedicated SCAD-CR program was the resultant decreased complaint of chest pain, higher exercise endurance, and decreased incidence of MACE and recurrent SCAD observed on follow-up [74].…”
Section: Cr Programsmentioning
confidence: 99%
“…An increasingly important cause of ACS is spontaneous coronary artery dissection (SCAD) which is defined as the spontaneous rupture of a coronary artery wall, not caused by trauma, iatrogenesis, or atherosclerosis, resulting in the formation of a false lumen and intramural hematoma (3)(4)(5).…”
Section: What Is Scad Definitionmentioning
confidence: 99%
“…A retrospective cohort study published by Feldbaum et al, demonstrated that there has been a significant rise in the usage of a conservative approach before 2013-2019 going from 35% to 89% (30). A recent systematic review demonstrated that the conservative approach has been deemed as the favored treatment modality (3). The reasons opposing invasive strategies are due to the fact that vessels that undergo dissection in SCAD spontaneously heal within 4-6 weeks and that revascularization procedures carry a significant rate of failure along with decreased outcomes (25,28).…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation